Pengaruh Model Pembelajaran Discovery Learning Terhadap Prestasi Belajar Peserta Didik Pada Pembelajaran Tematik Kelas V SD Negeri 01 Nangsri Kebakkramat Karanganyar Tahun Pelajaran 2022/2023 - Arwan Ade Putra; Hera Heru Sri Suryanti; Sarafuddin Sarafuddin (Departement of Mathematics Education, 2023)
The purpose of this study is to determine the influence of the Discovery learning model on students' learning achievement in Thematic Learning for Grade V students of SD Negeri 01 Nangsri Kebakkramat Karanganyar Academic Year 2022/2023 This research was conducted at SD Negeri 01 Nangsri Kebakkramat, Karanganyar. This study is a quantitative research with the Discovery learning model. The population of this study consisted of all Grade V students of SD Negeri 01 Nangsri Kebakkramat Karanganyar, totaling 27 students, and they were used as the research sample. Therefore, this study employed saturated sampling (using all members of the population). The data collection technique used in this study was the experimental method with pretest and posttest written tests to determine the influence of the Discovery learning model on students' learning achievement in Thematic Learning for Grade V. The data collection techniques included observation to gather information about the school, interviews with the school principal and class teachers to determine the learning conditions, tests to determine the limit of students' achievement, and documentation to obtain student data. The data analysis technique used the paired sample t- test.Based on the analysis of pretest and posttest scores, the average posttest score of the students showed a significant improvement, with an average pretest score of 64.00 and an average posttest score of 84.30. The data analysis using the paired sample t-test formula revealed a t-value of 20.030 and a significance value of 0.000. The t-value was then compared with the t-table value with degrees of freedom (df) = (N-1) = (27-1) = (26) at a 5% significance level, which is 2.056. Therefore, the t-value (20.030) > t-table value (2.056), and the sig value (0.000) < 0.005. Thus, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. This indicates that the Discovery learning model has an influence on students' learning achievement in Thematic Learning for Grade V of SD Negeri 01 Nangsri Kebakkramat, Karanganyar, in the academic year 2022/2023.